Motivational Factors in the Typical Display of Humor and Creative Potential: The Case of Malevolent Creativity - Perchtold-Stefan, Corinna M.; Fink, Andreas; Rominger, Christian; Papousek, Ilona (Frontiers in Psychology, 2020)
Research is still disputing if an individual's use of humor in everyday life is also indicative of their creative potential. To date, the focus has been mainly restricted to shared cognitive factors, while motivational aspects that may link the production of humor and of creative ideas have been largely neglected. Humor motivation implicates latent social goals the creator pursues through the use of humor. These goals can be benign or more malicious, and manifest in an individual's typical display of comic styles. While often overlooked, creativity often serves social functions as well, especially in common everyday situations. Similar to humor, creativity is typically regarded as beneficial for individuals and society. Yet, creative ideas may also originate from less prosocial goals. This is reflected in the concept of malevolent creativity, where novel ideas are generated to deliberately harm others. The present study investigated individuals’ typical display of humor, differentiated in eight distinct comic styles in relation to their productivity in a behavioral test for malevolent creativity and general creative potential (n = 106). Individuals with higher scores on comic styles that are affiliated with malicious interpersonal goals – such as hurting or upsetting others or demonstrating superiority over others – were more fluent in producing malevolent creative ideas in the malevolent creativity test. This finding shows that individual differences in humor motivation relate to the capacity of coming up with relevant creative ideas also outside the domain of humor. The pattern of relationships between humor motivation and general creative potential differed from that of malicious creativity and implied the comic style "wit" only, primarily adding to the notion of shared cognitive processes in the production of humor and creative ideas. The study offers a novel perspective for how the inclusion of motivational factors that are inherent to conceptualizations of humor may also benefit creativity research.